„Nagy tüzet kiált a tűzoltó”: Az 1956-os forradalommal összefüggő hallgatói fegyelmi eljárások a pécsi jogi karon és a pedagógiai főiskolán - Polyák, Petra (Per Aspera ad Astra, 2017)
The retaliations following the Hungarian Revolution of October 1956 reached the institutions of higher education at the end of April 1957. However, in Pécs the first disciplinary procedures had been started almost a month ahead of the central executive order, due to university-college party organizations, as well as the initial difficulties surrounding the Young Communist League. The reason behind this is that both the Hungarian Socialist Workers’ Party and the Hungarian Young Communist League movements found their position rather precarious in the movement, when they were founded in February-March, 1957. For them, the disciplinary procedures served as the primary tool to restore and expand their influence. While it allowed the regulation of the students and lecturers who opposed the restoration, it also made the old and new positions redistributive within the party and the youth organizations. The records of these disciplinary trials as well as the appeals of the students both confirm and support the historical conclusion that causal relationship between activity during and retribution after the Revolution was not essential. The conscious creation of an Enemy was evident to some of the accused students as well. (Translated by Dávid Molnár)